Predicting noncontact lower limb injury using lumbar morphology in professional Australian Football and rugby league players - Duhig, S.; Hajek, M.; Williams, M.; Bourne, M.; Roberts, L.; Morris, N.; Shield, A.; Mingin, C.; Headrick, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Non-contact lower limb injuries are common within the Australian Football League (AFL) and National Rugby League (NRL). Smaller (<8.5 cm2) lumbar multifidus at the fifth vertebra (LM L5) and larger (>8.2 cm2) quadratus lumborum (QL) cross-sectional area (CSA) have been associated with increased non-contact lower limb injury risk in AFL players. These associations have not been explored in an NRL cohort. This study will attempt to replicate previous research findings by confirming that muscle morphology is associated with non-contact lower limb injury.